Upaya Guru Dalam Pembelajaran Sains Anak Usia Dini Dengan Menggunakan Metode Ekperimens Di RA Masyithoh Sudagaran - Diana Ayu Kurnilia; Sultiyah; Hidayatul Munawaroh (Program Studi Pendidikan Islam Anak Usia Dini, 2024)
In early childhood education, 6 aspects of development must be developed, namely language, physical motor, cognitive, religious and moral values, art, and every child already has potential that must be developed. This research aims to determine the application of early childhood science learning using experimental methods at RA Masyithoh Sudagaran. The research method used is qualitative descriptive. By being directly involved in learning and data obtained from observations, interviews, observations, teacher discussions and documentation sourced from RA Masyithoh Sudagaran Sapuran. Collected data from which conclusions can be drawn. In this discussion the teacher must prepare the methods, tools and materials that will be used and before that the teacher carries out experiments first so that they can be an example for the children. The results of the research show that the use of experimental methods in science learning at RA Masyithoh Sudagaran Sauran, Wonosobo Regency can improve children’s ability to understand simple science concepts such as mixing colors, make children more active, build children’s interest and increase children’s motivation toward science learning, as well as knowledge and creative thinking.